Anti-corruption campaign in Nigeria (1999-2007) The politics of a failed reform - Enweremadu, David U. (WAPOSO Series, 2012)
After completing the transition from military to civilian rule, Nigeria began a comprehensive anti-corruption campaign in 1999. Some of the reforms included the establishment of new anti-corruption agencies, a comprehensive reform of the public sector, and a global search for (looted) funds stashed away in other countries. Despite being unprecedented in many ways, the implementation of these programmes soon faced numerous challenges. Among the most obvious was the lack of capacity among some of the major institutions charged with the implementation of the reforms due to inadequate financial support, limited human resources, legal lacunas, an ineffective criminal justice system and constitutional immunity granted to key officials. To this can be added a weak civil society and the non-engagement of sub-national authorities (states and local governments), that together suggest the glaring absence of an internal political coalition against corruption.